Bear and Human - Grimm, Oliver (Brepols, 2023)
Bears have, throughout human history, been admired and feared by humans in equal measure, with an interrelationship between the two species identifiable from pre-modern times through a wealth of material items, as well as from cult sites, sacral remains, images, and written sources. This unique interdisciplinary volume draws together sixty-four contributions by experts from across a range of fields in order to shed light on the complex connections between bears and humans in a period extending from the pre-modern into modern times, and across an area stretching from England into Russia. From bear biology (represented by work from the Scandinavian Brown Bear Research Project) and archaeo(zoo)logy to art history, and from history of religion to philology, the research gathered across this three-volume set explores a wide-range of subjects. Among them are the bear in biology, bears and animal agency, bear remains in graves and churches, the role of bears in religious beliefs (including berserker and bear ceremonialism), bears in literature, the philology underpinning why bear is a taboo word, and the image of the bear in rock art, as well as political iconography up to the present day. Together, these wide-ranging but closely thematic texts combine to produce a ground-breaking new work that will prove fundamental in understanding the human connection with this remarkable animal.